The effects of corporate social responsibility toward green human resource management: The mediating role of sustainable environment - Sadia Cheema (Taylor & Francis Group, 2017)
The perception of creating a sustainable environment by business entities is explored in this paper. The rising demand for Corporate Social Responsibility (CSR) leads to the application of management tools of green human resource management. Most organizations have adapted human resource practices that encourage a green environment with a consideration of minimal environmental pollution and destruction of the environment. As part of a conservation motive, the human resource department has played a critical role of securing the environment via their normal official activities. As a result, the senior management of an organization also an obligation of ensuring that the employees are supported as they seek to meet the social, ecological and economic benefits from a green environment. The idea of having a green environment by the human resource department is an integral process that affects the activities of green selection and recruitment, performance appraisal method, the reward and pay system and a supportive green culture. The importance of green environment is emphasized in the paper as well as the efforts by different companies in maintaining a sustainable environment. The expected outcomes of Green Human Resource Management (GHRM) are evaluated and the setbacks expected when trying to achieve a green environment.